2009
DOI: 10.1111/j.1365-2109.2008.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Na+, K+-ATPase-rich cells in the gill and urinary system of Persian sturgeon,Acipenser persicus, fry

Abstract: Localization of Na 1 , K 1 -ATPase-rich cells in the gill and urinary system of Acipenser persicus fry was performed through immuno£uorescence light microscopy using a mouse monoclonal antibody IgGa 5 raised against the a-subunit of chicken Na 1 , K 1 -ATPase. Di¡erent types of epithelia were clearly identi¢ed in the gill epithelium: epithelia of branchial arch, interbranchial septum, ¢lament and lamellar epithelium. The Na 1 , K 1 -ATPase-rich cells were found in the epithelia of branchial arch, interbranchia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Following embedment in Paraffin, transversal and longitudinal sections of 6 µm were cut on a Leica RM2255 microtome and collected on glass slides consecutively (all sections were collected) and stained with hematoxylin and eosin (Khodabandeh et al 2008). All histological slides were analyzed.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Following embedment in Paraffin, transversal and longitudinal sections of 6 µm were cut on a Leica RM2255 microtome and collected on glass slides consecutively (all sections were collected) and stained with hematoxylin and eosin (Khodabandeh et al 2008). All histological slides were analyzed.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…The possibility of improper acclimation to increased salinity, most probably due to ion regulation disfunctioning, has already been raised (Abdolhay and Tahori 2006). Blood osmotic pressure and morphology of the organs involved in osmoregulation have been determined for Persian sturgeons at different weights and especially for small juveniles: 2-3 g (Khodabandeh et al 2009a), 3.6 ± 0.2 g (Kazemi et al 2003), 125 ± 17.9 mg (Bahmani and Yousefi 2011), 206.6 ± 16.7 g (Kazemi et al 2003) and 245 ± 21.53 mg (Khatooni et al 2011). However, we still lack a thorough understanding of the cellular mechanisms allowing a complete acclimation to increased salinity.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two segments in the PT is irregular in the acipenserids (Gambaryan, 1988) as in other fishes. Only one segment was reported in the P. spathula (Krayushkina et al , 2000) and in the great sturgeon Huso huso (L. 1758) (Krayushkina et al , 1996 a ), but two segments were observed in several adult sturgeons (Gambaryan, 1988; Stoskopf, 1993; Krayushkina et al , 2000), and in A. persicus fry (Khodabandeh et al , 2009 a ). As stated by Krayushkina et al (2000)‘the presence of second proximal tubule (PT2) could be a distinctive feature of anadromous marine sturgeon,’ if the presence of PT2 is related to the migratory status of the species, more comparative studies on different species are needed to reach a definitive answer.…”
Section: Discussionmentioning
confidence: 99%
“…NKA is a ubiquitous membrane‐bound enzyme that actively transports Na + and K + through animal cells. It is important not only for sustaining intracellular homeostasis, but also for providing a driving force for many transporting systems in the fish gills and kidneys (Lin et al , 2004; Nebel et al , 2004, 2005; Zhou & Vize, 2004; Khodabandeh et al , 2009 a,b ). The abundance of ionocytes and of NKA affects the osmoregulatory capacity, which controls the ability of fishes to tolerate salinity and its fluctuations (Nebel et al , 2004).…”
Section: Introductionmentioning
confidence: 99%